60 divided by 4 is 15. so 2*15= 30 // 6*15= 90 // 8*15=120
Answer:
43 46 34 98 78 67
Step-by-step explanation:
<span>If you plug in 0, you get the indeterminate form 0/0. You can, therefore, apply L'Hopital's Rule to get the limit as h approaches 0 of e^(2+h),
which is just e^2.
</span><span><span><span>[e^(<span>2+h) </span></span>− <span>e^2]/</span></span>h </span>= [<span><span><span>e^2</span>(<span>e^h</span>−1)]/</span>h
</span><span>so in the limit, as h goes to 0, you'll notice that the numerator and denominator each go to zero (e^h goes to 1, and so e^h-1 goes to zero). This means the form is 'indeterminate' (here, 0/0), so we may use L'Hoptial's rule:
</span><span>
=<span>e^2</span></span>
Answer:
When you calculate the average rate of change of a function, you are finding the slope of the secant line between the two points. f(x) = x2 and f(x + h) = (x + h)2 Therefore, the slope of the secant line between any two points on this function is 2x + h.
Answer:
A) 113 m²
Step-by-step explanation:
Use the formula for area of a circle.
Area of a circle = πr²
π = pi = 3.14 (rounded)
r = radius
² = the power of 2, or the radius (in this case) multiplied by itself.
Note that the radius is given, and it is 6. Plug in 6 for the radius:
A (circle) = π(6)²
First, solve the power. Multiply 6²:
6² = 6 * 6 = 36
Next, multiply 36 with π (3.14):
36 x 3.14 = 113.04
A) 113 m² is your closest answer.
~